Enfrentamento em rede: a resistência das mulheres frente às inconsistências do Estado - Eugenio, Flavia Roberta (2023)
Participants in a historical process of social exclusion, discrimination, and violence, women have started to organize for social change. The recent decades have shown both progress and setbacks in the pursuit of guarantees and defense of women's rights. In Brazil, we have witnessed the establishment and expansion of Public Policies for Women and also initiatives to combat violence against women from the early 2000s until the mid-2015s. Subsequently, a political movement characterized by regression and the removal of rights has directly impacted the implementation of these policies, leading to the deterioration and dismantling of what had been built. The present research aimed to analyze the meanings produced in the implementation of public policies for addressing and combating violence against women in the city of São Paulo, focusing on the work of three Women's Defense and Coexistence Centers (CDCM). The research procedure and approach involved interviews with professionals who held technical positions (psychologists, social workers, and lawyers) in these services, which are part of the contracted network for addressing violence against women in the city of São Paulo (SP). Data analysis followed the Socio-Historical Psychology approach. Four main analytical categories were identified: 1. Inconsistencies of the State in Combating Violence against Women; 2. Women's Network in the Face of Public Policy Precariousness; 3. Political and Academic Training as a Foundation for Resistance; 4. We Belong to This Group. Additionally, the study was updated in the year 2022 to consider the context of the Covid-19 pandemic, including a new interview with one of the participants, which aimed to present considerations before and during the pandemic. Finally, the intention was to establish connections between these meanings and the Dimension of Subjectivity of Reality